Robust image hashing method from global perception features of human visual cortex - SUN Rui1; YAN Xiao-xing2; GAO Jun1 (Tongxin xuebao)
Firstly,the image was filtered low-passly and re-scaled to fixed size.Then the image was divided into key-dependent overlapping blocks.According to the hierarchical structure of HVS primary visual cortex,directional contour responses were extracted through layer-by-layer processing of visual pathway,and global perception features could be obtained by associating with the surface color of each blocks.These features included image direction and color information.The relation of adjacent entries was invariant to ordinary image processing.It could be used to quantize and permute these feature to get the binary image hash.Test results indicate that the proposed method is robust against con-tent-preserving modifications such as JPEG compression and filtering,at the same time,is capable of localizing image malicious tampering.Hashes of different images have very low collision probability.